Model Pembelajaran Kursus Tiket dan Reservasi di Perguruan Tinggi Pariwisata Indonesia - Rahmawati, Rahmawati; Rante, Margaretha Wadid (Universitas Negeri Makassar, 2021)
This research is a case study conducted at tourism universities, namely STP Bandung (Bandung Tourism College) and Poltekpar Makassar (Makassar Tourism Polytechnic). The research method used is descriptive qualitative research that uses 2 types of instruments in data collection, namely observation and interviews. The results of the study revealed that the Ticket Reservation course at the two universities was held through contextual learning with direct and contextual learning models applied to the learning process in the classroom, while direct learning was used for the learning process in the laboratory. The use of two learning models is determined by two factors, namely instructional objectives and student conditions. Overall, these findings suggest that the use of contextual learning and direct learning creates a conducive learning atmosphere and provides space for lecturers to improvise following the real conditions that occur in the teaching and learning process and their teaching tendencies as well as for students to develop their potential independently.